Evolution behavior of oxide inclusions in Si-Mn deoxidized steel during billet heating process (Journal of Mining and Metallurgy, Section B: Metallurgy, 2025)
To reduce the harm of oxide inclusions to the quality of Si-Mn deoxidized steel products, the effects of heat treatment temperature and isothermal heating time on the composition and morphology of inclusions are studied. The Si-Mn deoxidized steel LX82A billets are isothermal heating at 1000 °C, 1100 °C, 1200 °C for 8h, 10h and 12h, respectively. The results show that the  inclusions change from oval to round gradually with the increase of heat treatment temperature. When the heat treatment temperature rises to 1200 ℃, the oxide inclusions completely transform into MnO-SiO2-Al2O3 system. With the increase of heat treatment temperature, the MnO content in inclusions increases significantly. The SiO2 content increases first and then decreases. The CaO and Al2O3 content decreases obviously at 1200 ℃. The MgO content does not change significantly during the heat treatment process. When the heat treatment temperature is 1000 and 1100 ℃, the average composition of the oxide changes the most when the holding time is 10 h. When the holding time is 10 h, the average content of SiO2 increases and the average content of CaO decreases. Under the condition of heat treatment at 1100 ℃ for 10 h, the average content of MnO increases. When the heat treatment temperature reaches 1200 ℃, with the extension of holding time, the average content of the five components in the silicon-manganese deoxidized steel basically does not change.At a heating temperature of 1200°C, calcium treatment is facilitated, and the formation of a Mn-depleted zone occurs, thereby improving the steel quality and enhancing its performance. Moreover, oxide inclusions exhibit better deformability and lower melting points. Therefore, the heat treatment temperature should be maintained around 1200°C to optimize these properties.